Penggunaan Bahasa Indonesia dan Bahasa Gaul di Kalangan Remaja - Putri Rizki Rahmadhani; Edi Syaputra (Jurnal Multidisiplin Dehasen (MUDE), 2022)
Language is a communication tool used to interact, work together, and identify oneself in a society. The phenomenon of slang today is really unavoidable. This phenomenon is caused by the development of the communication style of the younger generation that has penetrated the barriers of space and time. Currently, the use of Indonesian, both in real life and fictional life, has begun to experience interference and has begun to shift to be replaced by the use of slang. Slang users in the wider community in Indonesia certainly have a negative impact on Indonesian language users properly and correctly. In addition, language is used to convey an idea, idea, opinion, feeling and thought to others. As well as a tool to develop themselves and socialize with others. A language must have a clear meaning so that when communication occurs, there is no misunderstanding in its delivery. Currently, there are several variations of the style of language used in the community. The variety of language styles is triggered by the development of communication technology which is growing very rapidly. The development of this language makes the style of language used by generation to generation is different. Each generation will have its own distinctive style of language. The use of good and correct Indonesian has now begun to be displaced by slang and feels accustomed to using slang.